Nutritional risk factors in patients with nasopharyngeal carcinoma: a cross-sectional study - Wang, Pengpeng; Huang, Xueling; Xue, Li; Liao, Jinlian; Liu, Jieying; Yu, Jiaxiang; Li, Ting (Frontiers in Nutrition, 2024)
Background: Patients with nasopharyngeal carcinoma are notably susceptible to high nutritional risks. If not addressed, this susceptibility can lead to malnutrition, resulting in numerous adverse clinical outcomes. Despite the significance of this issue, there is limited comprehensive research on the topic.Objective: The objective of our study was to identify nutritional risk factors in patients with nasopharyngeal carcinoma. Methods: For this cross-sectional study, we recruited a total of 377 patients with nasopharyngeal carcinoma. The Nutritional Risk Screening 2002 tool was used to assess their nutritional risk. These patients were divided into a well-nourished group (n = 222) and a nutritional risk group (n = 155). Potential risk factors were screened out using univariate analysis (p＜0.1). These factors were subsequently analyzed with multivariate logistic regression analysis (p＜0.05) to identify the nutritional risk factors for these patients.Results: Our findings indicated that increasing age (OR = 1.085, 95%CI: 1.053-1.117, p＜ 0.001), high number of radiation treatments (OR = 1.103, 95%CI: 1.074-1.132, p＜0.001), low BMI (OR = 0.700, 95%CI: 0.618-0.793, p＜0.001), and low albumin levels (OR = 0.852, 95%CI: 0.789-0.921, p＜0.001) are significant nutritional risk factors in patients with nasopharyngeal carcinoma.Conclusions: Increasing age, high number of radiation treatments, low BMI, and low albumin levels are significant nutritional risk factors in patients with nasopharyngeal carcinoma.